(untitled) (Research, Society and Development, 2021)
Swine Enzootic Pneumonia (PES) is an endemic disease in swine producing countries and can be found all over the world. Its etiological agent is the bacterium Mycoplasma hyopneumoniae, which is one of the main respiratory diseases in pigs. It plays an important role in animal health and is extremely important in swine production, especially in the growing and finishing phases, it is considered a factor of great damage with the condemnation of carcasses, increased use of medicines and decreased production performance, generating significant economic losses to the swine industry worldwide. Considering the importance of infection, the present work carried out a literature review on the main factors that favor infection, aiming to understand its biological, pathogenic, diagnostic, treatment and prophylaxis aspects. Knowledge of the forms of transmission is essential to understand its forms of dissemination, appropriate diagnostic techniques and disease prevention. Thus, it is extremely important to carry out research in order to reduce economic losses, through the correction of risk factors, therapeutic and immunoprophylactic measures.